Analysis of the Implementation of Wordwall Learning Media in Improving Elementary School Students' Science Learning Outcomes - Hanafi, Hanafi; Andayani, Andayani; Prabowo, Suryo (LPPM Universitas Pelita Bangsa, 2024)
Education is the main foundation in creating the potential of the younger generation. The success of the education system is determined by student learning outcomes. However, in the 5.0 era, the decline in student learning outcomes is a big problem that we must face, especially in science subjects. What can be done to improve student learning outcomes is to use effective learning media. The purpose of this study is to analyze the use of technology-based media, namely wordwall, in improving student learning outcomes. The method used is Systematic Literature Review (SLR) by searching for articles related to the keywords wordwall, learning outcomes, elementary school. The result of this study is the use of wordwall media can improve student learning outcomes. Then, the use of wordwall media makes students active in the learning process and the use of this application is free so that it is easy to use by all communities.)